Le concept de 'Nord' chez Xavier Marmier et ses prédécesseurs allemands - Damiens, Margot (HAL CCSD, 2018)
International audience This article contributes to the study of Xavier Marmier's ties to German educated circles and to the history of the concept of “North” by analysing the contents and evolutions of said concept in the Lettres sur le Nord (1840) and the four German travelogues about Scandinavia mentioned in them. These works stand in continuity to one another, following the aesthetic trends of their time to distance themselves from the traditional, negative depiction of the “North”. Its nature is instead praised for its beauty, associated with typical elements (pine trees, lakes) and compared to landscape paintings and the Alps, while its inhabitants are given a series of positive attributes (hospitality, strength, honesty…) explained by the climate, their isolation, and a specific Scandinavian essence. However, that positive appreciation has limits, both geographic and mental. While Marmier differs from his German predecessors by including Denmark and northern Germany in the “North”, he shares their ambivalence towards the Sami people and the regions beyond the polar circle, where vegetation and civilisation disappear. By doing so, he sticks to the values and ideology of the European elite, which might criticise “civilisation” in Rousseau's sense, but still rejects what stands outside of it.